Sessile serrated lesion detection rates during average risk screening colonoscopy: A systematic review and meta-analysis of the published literature - Desai, Madhav; Anderson, Joseph C.; Kaminski, Michael; Thoguluva Chandrasekar, Viveksandeep; Fathallah, Jihan; Hassan, Cesare; Lieberman, David; Sharma, Prateek (Endoscopy International Open, 2021)
Background and study aims Sessile serrated lesion (SSL) detection rate has been variably reported and unlike adenoma detection rate (ADR) is not currently a quality indicator for screening colonoscopy. Composite detection rates of SSL in patients undergoing average risk screening colonoscopy are not available.Methods Electronic database search (Medline, Embase and Cochrane) was conducted for studies reporting detection rates of serrated polyps (SSL, Hyperplastic polyp, traditional serrated adenoma) among average risk subjects undergoing screening colonoscopy. Primary outcomes were pooled SDR (SSL detection rate) and proximal serrated polyp detection rate (PSPDR). Pooled proportion rates were calculated with 95 %CI with assessment of heterogeneity (I2). Publication bias, regression test and 95 %prediction interval were calculated.Results A total of 280,370 screening colonoscopies among average risk subjects that were eligible with 48.9 % males and an average age of 58.7 years (± 3.2). The pooled SDR was available from 16 studies: 2.5 % (1.8 %–3.4 %) with significant heterogeneity (I2 = 98.66 %) and the 95 % prediction interval ranging from 0.6 % to 9.89 %. When analysis was restricted to large (n > 1000) and prospective studies (n = 4), SDR was 2 % (1.1 %–3.3 %). Pooled PSPDR was 10 % (8.5 %–11.8 %; 12 studies). There was evidence of publication bias (P < 0.01).Conclusion Definitions of SSL have been varying over years and there exists significant heterogeneity in prevalence reporting of serrated polyps during screening colonoscopy. Prevalence rate of 2 % for SSL and 10 % for proximal serrated polyps could serve as targets while robust high-quality data is awaited to find a future benchmark showing reduction in colorectal cancer arising from serrated pathway.